2012
DOI: 10.1063/1.4769836
|View full text |Cite
|
Sign up to set email alerts
|

4-fold enhancement in the critical current density of YBa2Cu3O7 films by practical ion irradiation

Abstract: We report an up-to-4-fold enhancement in the in-magnetic-field critical current density at 77 K of epitaxial YBa 2 Cu 3 O 7 films on CeO 2 -buffered SrTiO 3 substrates by 3-MeV Au 2þ irradiation. This indicates that irradiation using an industrially practical ion beam, which generally has kinetic energy less than 5 MeV, can provide a substantial increase in the in-field current performance of high-temperature superconductor films. Transmission electron microscopy results show that pointlike defects smaller tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
45
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(50 citation statements)
references
References 28 publications
4
45
0
1
Order By: Relevance
“…Essentially the same results were obtained at 0.1 and 1 T where we performed θ-dependent measurements. As we reported previously [1], MeV-ion irradiation on a FF-MOD film enhances J c more significantly at H // c than H // ab [figures 2(a) and 2(d)]. This basic anisotropy trend is also found in figures 2(b) and 2(e), suggesting that the same type of pinning centers were introduced by the irradiation in FF-MOD and TCE films, although the width of J c enhancement is largely different between the two.…”
Section: Resultssupporting
confidence: 76%
See 2 more Smart Citations
“…Essentially the same results were obtained at 0.1 and 1 T where we performed θ-dependent measurements. As we reported previously [1], MeV-ion irradiation on a FF-MOD film enhances J c more significantly at H // c than H // ab [figures 2(a) and 2(d)]. This basic anisotropy trend is also found in figures 2(b) and 2(e), suggesting that the same type of pinning centers were introduced by the irradiation in FF-MOD and TCE films, although the width of J c enhancement is largely different between the two.…”
Section: Resultssupporting
confidence: 76%
“…J c data was collected by a nondestructive ac inductive method at the liquid nitrogen temperature [6]. All J c data of FF-MOD films was presented in our previous publication [1].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…With respect to J c at self-field, the retained J c at 3 T is ∼19.5%, and ∼13.4% at 5 T, values much higher than the values of 10.9% at 3 T and 3.4% at 5 T measured in the 7.5% Zr-doped film. J c remains above 0.1 MA/cm 2 , a threshold value for applications, 4 up to 8 T. Meanwhile, J c of the 15% Zr-doped thin film exceeds that of Au-ion irradiated YBCO films at field above 2 T, 25 and the recently reported J c of proton-irradiated metal organic deposited (MOD) thin films above 6.5 T. sample is its extremely high H irr (77 K) ≈ 14.8 T, about 45% higher than that of the 7.5% Zr-doped film, and much higher than ∼9 T shown by nominally pure films.…”
mentioning
confidence: 99%
“…These defects produced by ion irradiation would account for the depression of T c in YBa 2 Cu 3 O y (YBCO), which is proportional to the average number of defects23. Recently, a low-energy ion irradiation has been revisited and suggested as a practically feasible approach to improve flux pinning in YBCO242526. In single crystals of iron-based superconductors, it has been found that ion irradiations, as a whole, improve J c and its J c enhancements persist up to much higher fluencies than in cuprate superconductors, although T c is suppressed with increasing irradiation doses272829.…”
mentioning
confidence: 99%